Causal Relationships Between Osteoarthritis and Senile Central Nerve System Dysfunction: A Bidirectional Two-Sample Mendelian Randomization Study - Cai, Yuanqing; Zhang, Guangyang; Liang, Jialin; Jing, Zhaopu; Zhang, Rupeng; Lv, Leifeng; Dang, Xiaoqian (Frontiers in Aging Neuroscience, 2022)
Background The relationship between osteoarthritis (OA) and senile central nervous system dysfunctions (CNSDs), including Parkinson’s disease (PD), Alzheimer’s disease (AD), and ischemic stroke (IS) has gradually attracted attention. At present, the causal relationship between OA and CNSD remains unclear. The aim of this study was to assess the causal effects of CNSD and OA using Mendelian randomization (MR). Methods Genome-wide association study summary data for CNSD and OA were obtained. Single-nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs), and significant (P < 5.0 × 10–8) and independent (r2 < 0.1) SNPs were extracted for bidirectional MR analysis. Inverse variance weighted (IVW) was used to assess these causal relationships. The results are reported as odds ratios (ORs). Subsequently, heterogeneity was tested using the Cochran’s Q test, pleiotropy was tested using the MR-Egger intercept, and sensitivity analysis was performed using the leave-one-out sensitivity test. Results The MR results of the causal relationship between PD and OA showed that there was a positive causal effect of OA on PD, which was estimated by IVW (OR = 1.194, 95%CI = 1.036, 1.378; P = 0.0144). Moreover, the MR analysis by IVW also showed that IS had a positive effect on OA (OR = 1.033, 95%CI = 1.002, 1.066; P = 0.0355). These results are reliable and stable, as confirmed by sensitivity tests. Conclusion This study showed a positive causal effect of OA on PD, but there was a null effect of OA on AD and OA on IS.